2022
DOI: 10.1088/1741-4326/ac9196
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of alpha particles on the transport of helium ash driven by collisionless trapped electron mode turbulence

Abstract: The effects of alpha (α) particles on the transport of helium ash driven by collisionless trapped electron mode (CTEM) turbulence are analytically studied using quasi-linear theory in tokamak deuterium (D) and tritium (T) plasmas. Under the parameters used in this work, the transport of helium ash is mainly determined by the diffusion due to very weak convection. It is found that the ratio between helium ash diffusivity and effective electron thermal conductivity (D_He/χ_eff) driven by CTEM turbulence, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Weixin Guo et al presented the helium ash transport driven by collisionless trapped electron mode (CTEM) turbulence in the presence of alpha (α) particles. They found that although D He /χ eff <1, which was less efficient for the removal of helium ash as compared with ITG mode [20], D He /χ eff could be increased by 50% with the presence of 3% α particles with their density gradient being twice that of electrons [21]. This is mainly because the destabilizing effect of α particles [22] on helium ash diffusivity is stronger than that on electron thermal conductivity.…”
Section: Micro-turbulence and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Weixin Guo et al presented the helium ash transport driven by collisionless trapped electron mode (CTEM) turbulence in the presence of alpha (α) particles. They found that although D He /χ eff <1, which was less efficient for the removal of helium ash as compared with ITG mode [20], D He /χ eff could be increased by 50% with the presence of 3% α particles with their density gradient being twice that of electrons [21]. This is mainly because the destabilizing effect of α particles [22] on helium ash diffusivity is stronger than that on electron thermal conductivity.…”
Section: Micro-turbulence and Transportmentioning
confidence: 99%
“…Xiaolong Zhu presented the hybrid simulation of the avalanche transport of energetic particles observed in National Spherical Torus eXperiment (NSTX), which was believed to be a strong nonlinear process, leading to significant EP transport. It is found that the existence of multiple modes and the overlapping of their phase-space wave-particle resonance region are crucial for the onset of avalanche EP transport [35].…”
Section: Energetic Particle Physicsmentioning
confidence: 99%